Optimization Of Anesthetic Management For Gynecological Operations - Khudoyberdieva Gulrukh Sobirjonovna (Academia One, 2024)
In recent years, in the Department of gynecology, often performed extirpation of the uterus. This is due to the fact that drug therapy does not give the desired effect. Only according to the multidisciplinary clinic of SamMU only in 2022, constituent part of extirpation of the all 150 laparotomic operations, uterine fibroids accounts about for 56.2%.
Keywords: methods; laparotomic; operations